INCLUSIVE SCHOOL MANAGEMENT TO IMPROVE THE QUALITY OF LEARNING FOR CHILDREN WITH LEARNING DIFFICULTIES - Selvia Wulandari; R. Madhakomala (Ravine Publisher, 2024)
The background of this study is to dive deeper into the management of inclusive schools as well as to understand how school management programs can be effectively implemented and their impact on the learning quality of children with learning difficulties. This study aims to describe and analyze how the management process in inclusive schools can help improve the learning quality of children with learning difficulties. The method used in this study is qualitative research with a literature study approach. The results of this study indicate that inclusive schools are institutions that provide educational services for all students, including those with special needs, in the same learning environment. Inclusive schools aim to provide opportunities for children with special needs to optimize their respective potentials through a quality learning process. To achieve this goal, there is a need for effective implementation of inclusive school management. The implementation of inclusive school management has an impact on the learning quality of students with learning difficulties.